1984
DOI: 10.1111/j.2042-7158.1984.tb04391.x
|View full text |Cite
|
Sign up to set email alerts
|

The opioid κ-selective compound U−50,488H does not inhibit intestinal propulsion in rats

Abstract: The selective kappa-compound U-50,488H, at doses producing strong central pharmacological effects (0.5-32 mg kg-1 i.p.) did not delay the intestinal transit of a charcoal meal and had little or no antagonist action against morphine-induced constipation. It appears that kappa-opioid receptors are probably not involved in the mechanisms responsible for opioid-induced constipation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 7 publications
0
13
0
Order By: Relevance
“…In addition to antinociception, a slowed gut transit is characteristic of late pregnancy [4]. Of particular importance, here, are the findings that pregnancy antinociception is mediated by n-opioid [26] and y-opioid [5] receptors, that the opioid-based slowing of gut transit is mediated by A-opioid receptors [2,12,23,24,28], and that ingested placenta enhances n-and yreceptor-mediated antinociception but inhibits A-receptormediated antinociception [7]. Therefore, as suggested by the present results, ingestion of placenta or amniotic fluid at parturition may enhance the antinociception of pregnancy as well as help restore normal gut transit after parturition, particularly when transit has been slowed by activity at Aopioid receptors in the CNS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to antinociception, a slowed gut transit is characteristic of late pregnancy [4]. Of particular importance, here, are the findings that pregnancy antinociception is mediated by n-opioid [26] and y-opioid [5] receptors, that the opioid-based slowing of gut transit is mediated by A-opioid receptors [2,12,23,24,28], and that ingested placenta enhances n-and yreceptor-mediated antinociception but inhibits A-receptormediated antinociception [7]. Therefore, as suggested by the present results, ingestion of placenta or amniotic fluid at parturition may enhance the antinociception of pregnancy as well as help restore normal gut transit after parturition, particularly when transit has been slowed by activity at Aopioid receptors in the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Another effect of central or systemic opioids is a slowing of gut transit [3,6,15], which is believed to be mediated by A-opioid receptor activity both centrally and peripherally [2,12,23,24,28]. This is believed to occur centrally by action in the dorsal vagal complex of the hindbrain [10], which is part of the vagovagal neurocircuitry that influences gastrointestinal function [11], yet it is believed to occur peripherally by disruption of the role of local opioids in intestinal muscular contraction and relaxation [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…All three types are present in the intestinal wall of the rat Dashwood et al, 1985;Fickel et al, 1997;Gray et al, 2005;Nishimura et al, 1986;Sternini et al, 1995). A and y receptor activation each lead to gastrointestinal transit arrest in the rat (La Regina et al, 1988;Tavani et al, 1984Tavani et al, , 1990, and our group has recently shown that these receptors mediate inhibition of electrically induced neurogenic smooth muscle contractions in the rat ileum (Gray et al, 2005). A receptors also appear to mediate anti-secretory effects (Coupar, 1983).…”
Section: Introductionmentioning
confidence: 90%
“…The -opioid receptor distributions in the brain and gastrointestinal tract of humans and guinea pigs are similar, with respect to both overall receptor distribution and the prevalence of the high-affinity receptor subtype. For some aspects of the opioid system, the guinea pig may therefore prove to be a better animal model than the rat, which has a lower overall abundance of -opioid receptors that are primarily of the low-affinity subtype (18,63,78).We report here on the isolation and sequencing of the guinea pig preproenkephalin gene and its expression in the brain. Unexpectedly, we have also identified a site-specific cleavage in the 3Ј untranslated region (3Ј UTR) of preproenkephalin mRNA which yields 3Ј-truncated transcripts in specific brain regions, including the caudate putamen, nucleus accumbens, and amygdala.…”
mentioning
confidence: 99%
“…The -opioid receptor distributions in the brain and gastrointestinal tract of humans and guinea pigs are similar, with respect to both overall receptor distribution and the prevalence of the high-affinity receptor subtype. For some aspects of the opioid system, the guinea pig may therefore prove to be a better animal model than the rat, which has a lower overall abundance of -opioid receptors that are primarily of the low-affinity subtype (18,63,78).…”
mentioning
confidence: 99%